ANALYSIS OF POSSIBLE REASONS OF FOMIATION OF NODULAR CEMENTITE IN STRUCTURE OF WIRE OF HIGH-CARBON STEEL IN CONDITIONS OF HARDWARE PRODUCTION OF RUP “BMZ” - T. P. Kurenkova; I. V. Borisovets (Литьë и металлургия, 2008)
The possible reasons of nodular cement formation in structure of wire-slug for production of metal cord and wire RVD are determined and systematized